A Fluorescent Ditopic Rotaxane Ion‐Pair Host. Issue 19 (5th March 2018) - Denis, Mathieu; Qin, Lei; Turner, Peter; Jolliffe, Katrina A.; Goldup, Stephen M.
Abstract: We report a rotaxane based on a simple urea motif that binds Cl − selectively as a separated ion pair with H + and reports the anion binding event through a fluorescence switch‐on response. The host selectively binds Cl − over more basic anions, which deprotonate the framework, and less basic anions, which bind more weakly. The mechanical bond also imparts size selectivity to the ditopic host. Abstract : It takes two : A simple fluorescent axle combined with a bipyridine macrocycle produces a ditopic rotaxane host that binds a separated HX ion pair strongly but not the anion alone. The rotaxane selectively binds Cl − over more basic anions, which deprotonate the framework, or less basic anions, which bind more weakly. The mechanical bond also confers size selectivity on the ditopic host.